Coenzyme Q Biosynthesis: Evidence for a Substrate Access Channel in the FAD-Dependent Monooxygenase Coq6 - Ismail, Alexandre (PLoS Comput Biol, 2016)
Coq6 is an enzyme involved in the biosynthesis of coenzyme Q, a polyisoprenylated benzoquinone lipid essential to the function of the mitochondrial respiratory chain. In the yeast Saccharomyces cerevisiae, this putative flavin-dependent monooxygenase is proposed to hydroxylate the benzene ring of coenzyme Q (ubiquinone) precursor at position C5. We show here through biochemical studies that Coq6 is a flavoprotein using FAD as a cofactor. Homology models of the Coq6-FAD complex are constructed and studied through molecular dynamics and substrate docking calculations of 3-hexaprenyl-4-hydroxyphenol (4-HP6), a bulky hydrophobic model substrate. We identify a putative access channel for Coq6 in a wild type model and propose in silico mutations positioned at its entrance capable of partially (G248R and L382E single mutations) or completely (a G248R-L382E double-mutation) blocking access to the channel for the substrate. Further in vivo assays support the computational predictions, thus explaining the decreased activities or inactivation of the mutated enzymes. This work provides the first detailed structural information of an important and highly conserved enzyme of ubiquinone biosynthesis.